2021
DOI: 10.31729/jnma.7047
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive Protein to Albumin Ratio among Patients Admitted to Intensive Care Unit of a Tertiary Care Hospital: A Descriptive Crosssectional Study

Abstract: Introduction: Sepsis is the most common cause of mortality among patients admitted to intensive care unit. There is emerging evidence on the role of C-reactive protein to albumin ratio (C-reactive protein/Albumin) in predicting outcomes in patients with critical illness and sepsis, admitted to intensive care unit. We aimed to find out the median value of C-reactive protein/Albumin ratio among patients admitted to intensive care unit of a tertiary care hospital. Methods: We conducted a descriptive cross-section… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Results of the present study suggested that CAR was associated with the prognosis in patients treated in ICU. Accordingly, in a recent study by Gyawali et al, it has been suggested that CAR could be useful in determining patients with a high risk of sepsis development (12). In contrast, CAR levels of survivals and nonsurvivals were not statistically different in ICU subjects with sepsis (13).…”
Section: U N C O R R E C T E Dmentioning
confidence: 96%
“…Results of the present study suggested that CAR was associated with the prognosis in patients treated in ICU. Accordingly, in a recent study by Gyawali et al, it has been suggested that CAR could be useful in determining patients with a high risk of sepsis development (12). In contrast, CAR levels of survivals and nonsurvivals were not statistically different in ICU subjects with sepsis (13).…”
Section: U N C O R R E C T E Dmentioning
confidence: 96%